(-n+(-3))-(8n+(-2))=

Simple and best practice solution for (-n+(-3))-(8n+(-2))= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-n+(-3))-(8n+(-2))= equation:


Simplifying
(-1n + (-3)) + -1(8n + (-2)) = 0
(-1n + -3) + -1(8n + (-2)) = 0

Reorder the terms:
(-3 + -1n) + -1(8n + (-2)) = 0

Remove parenthesis around (-3 + -1n)
-3 + -1n + -1(8n + (-2)) = 0
-3 + -1n + -1(8n + -2) = 0

Reorder the terms:
-3 + -1n + -1(-2 + 8n) = 0
-3 + -1n + (-2 * -1 + 8n * -1) = 0
-3 + -1n + (2 + -8n) = 0

Reorder the terms:
-3 + 2 + -1n + -8n = 0

Combine like terms: -3 + 2 = -1
-1 + -1n + -8n = 0

Combine like terms: -1n + -8n = -9n
-1 + -9n = 0

Solving
-1 + -9n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -9n = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -9n = 0 + 1
-9n = 0 + 1

Combine like terms: 0 + 1 = 1
-9n = 1

Divide each side by '-9'.
n = -0.1111111111

Simplifying
n = -0.1111111111

See similar equations:

| 12b+5=b-303 | | 13x^2+10x-3=0 | | a=(x-2)(x-1) | | (8n+4)-(n+(-2))= | | 5m+4m-28=45 | | 24-4x=15x | | b-36.9=5.1b | | 3m+1=4-6 | | -16(-19+11r)-18= | | -(6+5r)=-6-5r | | 635-35= | | (9n+1)-(6n+(-2))= | | d-182=-5d-8 | | (-3n+1)-(-5n+8)= | | A=x^2-3x+2 | | 5x+4(9x+4)=32 | | -20p+16=-9p-18-13p | | 3x^7+3x-15=0 | | 9-ln(5-x)=0 | | x^2-8x+16=-2 | | 6+2p-4=7p+11-4p | | -2x-14=6 | | 9+11a=-5a+12 | | (3n+1)-(5n+(-7))= | | n+137=-2n-4 | | 4d-5=0 | | 4y+(y+35)=180 | | p(x)=(x-(2-3i))(x-(2+3i)) | | 0=12x^2-40x-32 | | (-7n+(-3))-(-9n+5)= | | 18m-14=18m+18+2m | | -6+4=14y-10-13y |

Equations solver categories